THE THEORETICAL BASIS FOR MAHAYANA PLURALISM IN ASANGA’S MAHAYANASAMGRAHA - Hanson, Mervin V (Journal of Dharma, 1981)
At the heart of a pluralistic society or tradition are the theories which relate each of the various religious orientations to a common goal or ideal. These are as necessary for integrating different religious orientations within one catholic tradition, as for different religions within one pluralistic society. In this article J will show how the early Buddhist Vijñânavâdin masters devised theories to harmonize a contradictory mass of early beliefs.